2012
DOI: 10.1152/ajprenal.00749.2010
|View full text |Cite
|
Sign up to set email alerts
|

High glucose-induced RhoA activation requires caveolae and PKCβ1-mediated ROS generation

Abstract: Ingram AJ, Krepinsky JC. High glucose-induced RhoA activation requires caveolae and PKC␤1-mediated ROS generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
(102 reference statements)
4
24
0
Order By: Relevance
“…Given that PKCβ 1 activation induced by HG requires caveolae in primary mesangial cells (32), we determined whether caveolae are crucial in HG-induced PKCβ 2 activation in isolated cardiomyocytes from nondiabetic rats. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that PKCβ 1 activation induced by HG requires caveolae in primary mesangial cells (32), we determined whether caveolae are crucial in HG-induced PKCβ 2 activation in isolated cardiomyocytes from nondiabetic rats. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it was shown that high glucose can lead to PKC β 1-mediated ROS generation through NADPH oxidase with subsequent RhoA activation in mesangial cells. This RhoA in turn activates downstream AP-1 through Rho kinase leading to activation of TGF- β 1 [195]. In consistency with these observations, Weigert et al [196] demonstrated that AP-1 activation is responsible for increased TGF- β 1 expression through PKC- and p38-MAPK-dependent pathways.…”
Section: Progression Of Renal Injury Through Diverse Signaling Patmentioning
confidence: 85%
“…Cav-1 is a major multifunctional scaf- folding protein of caveolae that serves as a negative or positive modulator of cell signaling pathways by directly interacting with signaling molecules [28,29] . Cav-1 is an important regulatory molecule in the kidneys that is primarily expressed in mesangial cells [17,[30][31][32] , renal proximal tubule cells [33,34] and podocytes [35] . Recently, many studies have demonstrated that the functional connections between cav-1 and ROS play a key role in many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez-Outschoorn et al demonstrated that a loss of stromal cav-1 in fibroblasts was sufficient to induce ROS production and oxidative stress, indicating that a loss of cav-1 provided a feed-forward mechanism for promoting oxidative stress and the autophagic program [37][38][39] . Zhang et al showed that glucose-induced ROS generation was significantly attenuated by the chemical disruption of caveolae in knockout mesangial cells [30] . Shiroto et al showed that mitochondrial ROS production was increased in endothelial cells after cav-1 knockdown, and their results established that cav-1 plays a key role in regulating oxidative stress in the endothelium and may represent a critical target in cardiovascular diseases [40] .…”
Section: Discussionmentioning
confidence: 99%